Overexpression of wip1 is associated with biologic behavior in human clear cell renal cell carcinoma. - Sulai Liu (PLoS ONE, 2014)
Wild-type p53-induced phosphatase (Wip1 or PPM1D) has been reported to be aberrantly expressed in various cancers and correlated with the malignant behavior of cancer cells. However, the function of Wip1 in RCC remains unclear. The present study investigated its abnormal expression and dysfunctions in clear cell renal cell carcinoma (ccRCC) in vitro. With the combination of immunohistochemistry, western blotting, immunofluorescence, qRT-PCR, and cell proliferation, migration and invasion assays, we found that levels of Wip1 mRNA and protein were dramatically increased in human ccRCC tissues (P<0.001 for both), and upregulation of Wip1 was significantly associated with depth of invasion (P<0.001), Distant metastasis (P = 0.001), lymph node status (P<0.001) and Fuhrman grade (P<0.001). Wip1 knockdown inhibited the proliferation, migration and invasion of 786-O and RLC-310 cells, whereas Wip1 overexpression promoted the growth and aggressive phenotype of 786-O and RLC-310 cells in vitro. The uni- and multivariate analyses indicated that expression of Wip1 was an independent predictor for survival of ccRCC patients (P = 0.003, P = 0.027 respectively). Wip1- negative patients had a higher tumor-free/overall survival rate than patients with high Wip1 expression (P = 0.001, P = 0.002 respectively). Overexpression of Wip1 is useful in the prediction of survival in ccRCC patients.